New Settlements in Bishkek: Law, Urban Space, Culture and Socio-Economic Development - Alymbaev, Mirlan (Ethnographica et Folkloristica Carpathica, 2022)
In Kyrgyzstan, internal migrants in search of a better life left high mountains, clean air, and their native village. There are tens of thousands of such people around the capital city of Bishkek. Physically, they are in the capital in the status of city dwellers, but living conditions, the level of access to public services are at the level of remote regions. And this is how these internal migrants live for tens of years, a new generation of children is growing up who were born in these slums where lack of infrastructure such as schools, drinking water, medical facility, electricity, and transport.This study is aimed to explore the living conditions of residents in the new settlements and their rights for decent housing. The study was prepared in order to attract the attention of the state authorities to solve the urgent problems of the residents.